2011
DOI: 10.1152/ajpcell.00332.2010
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing splanchnic nerve and chromaffin cell stimulation in mouse adrenal slices with fast-scan cyclic voltammetry

Abstract: Electrical stimulation is an indispensible tool in studying electrically excitable tissues in neurobiology and neuroendocrinology. In this work, the consequences of high-intensity electrical stimulation on the release of catecholamines from adrenal gland slices were examined with fast-scan cyclic voltammetry at carbon fiber microelectrodes. A biphasic signal, consisting of a fast and slow phase, was observed when electrical stimulations typically used in tissue slices (10 Hz, 350 μA biphasic, 2.0 ms/phase puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…) and for the detection of bulk catecholamine release from mouse adrenal slices (Walsh et al. ). Here, we extend this technique by calibrating signals against standard solutions and by separating signal characteristic for catecholamine species in an ex vivo, intact splanchnic–adrenal experimental preparation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and for the detection of bulk catecholamine release from mouse adrenal slices (Walsh et al. ). Here, we extend this technique by calibrating signals against standard solutions and by separating signal characteristic for catecholamine species in an ex vivo, intact splanchnic–adrenal experimental preparation.…”
Section: Resultsmentioning
confidence: 99%
“…We adapted a fast scanning cyclic voltammetry (FSCV) method for measuring separately the release of epinephrine (Epi) and norepinephrine (NE) under native neuronal stimulation. FSCV has been used to qualitatively measure release of catecholamine species from isolated bovine chromaffin cells (Pihel et al 1994) and for the detection of bulk catecholamine release from mouse adrenal slices (Walsh et al 2011). Here, we extend this technique by calibrating signals against standard solutions and by separating signal characteristic for catecholamine species in an ex vivo, intact splanchnic-adrenal experimental preparation.…”
Section: In Vitro Fast Scanning Cyclic Voltammetry Of Epinephrine Vermentioning
confidence: 99%
“…Wightman and colleagues have recently shown that this process is modulated by specialized receptors . Moreover, they have shown that amperometry can distinguish between signals arising from unselective electrical stimulations (cells vs peripheral nerves) …”
Section: Microelectrodes For Direct Neurotransmitter Detectionmentioning
confidence: 99%
“…In this study, a novel adaptation of a dynamic approach for electrochemical detection of NE levels in vivo is presented. The approach is based on fast scanning cyclic voltammetry (FSCV), a method utilized to measure catecholamine release from isolated cells ( 21 , 25 ) or from tissues ( 16 , 30 , 33 ). Briefly, an electrode is placed near the source of the transmitter and its potential driven though the oxidation/reduction potentials by a voltage clamp circuit.…”
Section: Introductionmentioning
confidence: 99%